The Effect of Training and Work Experience on Performance with Competence as an Intervening Variable at the Head of the Technical Implementation Unit of PT. Indonesian Railways - Mohamad Varis Purnomo; Badia Perizade; Yuliani Syapril (Ridwan Institute, 2023)
This research aims to examine the effect of training, work experience, and competence on performance, as well as identify whether competence acts as an intervening variable between training and performance, as well as between work experience and performance. The purpose of this research is to provide a better understanding of the factors that affect individual performance in the workplace. This research uses a quantitative approach by collecting data through questionnaires distributed to respondents who are employees in various organizations. The collected data is analyzed using statistical analysis methods such as regression analysis and path analysis to test the proposed hypothesis. The results show that training has a positive significant influence on performance, which supports the H1 hypothesis. In addition, work experience also has a positive significant influence on performance, which supports the H2 hypothesis. Competence was also found to have a positive significant influence on performance, supporting the H3 hypothesis. Furthermore, training also has a positive significant influence on competence, supports the H4 hypothesis, and work experience also has a positive significant influence on competence, supports the H5 hypothesis. In addition, the research results also support the H6 and H7 hypotheses, which state that training and work experience have a significant effect on performance through competence as an intervening variable.